PAPULES CAUSED BY DERMAL INFILTRATE. Acrodermatitis. EPIDERMAL PAPULES. FOLLICULAR PAPULES. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Papular acrodermatitis of childhood (Gianotti-Crosti syndrome). The disease is an acro-located dermatitis which is morphologically characterized by monomorphous papules and is due to a viral infection affecting the skin and the reticuloendothelial system, in particolar the liver. As other viral infections, the disease is not uniformly distributed. lt is quite frequent in Japan and in some countries situated in central Europe, whereas it is rarely reported in other countries. (...).